Factors Affecting Students’ Satisfaction in Design Courses; A Case Study of University Students in Chengdu, China - Zhao, Heyu; Qizhen, Gu (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
The purpose of this study is to investigate how students’ satisfaction is affected by six independent variables: namely perceived value, teaching quality, learning resources, instructors, course content, and technology. The study mainly adopts the questionnaire survey method, comprehensive research combining quantitative and qualitative approaches, to explore the factors influencing the satisfaction of students majoring in design at Sichuan University of Media and Communications (SUMC), and to improve students’ satisfaction by implementing strategic plans. Cronbach’s Alpha was employed as a pilot test (n=30) and the Item-Objective Congruence (IOC) was employed to assess the validity of this study. Then, 90 valid questionnaires were collected from SUMC. Multiple linear regression was used to analyze the quantitative data to verify the hypotheses. Subsequently, a group of 30 students participated in the implementation of a strategic plan for 16 weeks. The strategic plan stage was designed based on the results of multiple linear regression. Data were collected through questionnaires and structured interviews, and then the paired samples t-test was used to compare the results of the quantitative data before and after the strategic planning. Multiple linear regression results show that perceived value, teaching quality, learning resources, and instructors have significant effects on student satisfaction, while course content and technology have no significant effects on student satisfaction. Finally, the comparison results of the paired sample T-test show significant differences in perceived value, teaching quality, learning resources, and instructors in the post-strategic and pre-strategic planning stages.